2016
DOI: 10.1515/pjvs-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

The effects of freezing on long-term storage of canine erythrocytes

Abstract: Human medicine studies have so far demonstrated that erythrocytes may be preserved and stored at low temperatures for decades retaining their metabolic and biochemical properties. However, detailed studies regarding this problem are not yet available in veterinary medicine. Therefore, the objective of the current study was to investigate time-dependent effects of long-term frozen storage of canine red blood cells.Twelve healthy adult dogs meeting the criteria for blood transfusion were used in the study. Whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
1
Order By: Relevance
“…Reports of bacterial contamination of blood units in veterinary medicine are less frequently described than in human medicine, likely because fresh platelet transfusions are less common in veterinary medicine. Percentage of negative bacteriological units was high (94-100%) in studies on feline [131][132][133][134][135][136] and canine blood and plasma products [137][138][139][140] .…”
Section: Veterinary Literaturementioning
confidence: 99%
“…Reports of bacterial contamination of blood units in veterinary medicine are less frequently described than in human medicine, likely because fresh platelet transfusions are less common in veterinary medicine. Percentage of negative bacteriological units was high (94-100%) in studies on feline [131][132][133][134][135][136] and canine blood and plasma products [137][138][139][140] .…”
Section: Veterinary Literaturementioning
confidence: 99%
“…The transport of oxygen in the body all depends on the affinity of hemoglobin with oxygen. In the case of high partial pressure of oxygen, oxygen is easy to combine with hemoglobin, while in the case of low partial pressure of oxygen, oxygen and hemoglobin are easily dissociated [17]. It can be seen from Figure 2A that the oxygen partial pressure of red blood cells decreased gradually with the extension of storage time, which indicated that the effective oxygen carrying and oxygen releasing capacity of red blood cells decreased.…”
Section: Identification Of Oxygen Carrying Capacitymentioning
confidence: 95%
“…The slow cooling (40% glycerol concentration) showed quite a high effi ciency (70-80% survival) for canine erythrocytes [1].…”
Section: метод гіпотермічного зберігання дозволяє використовувати ком...mentioning
confidence: 99%
“…Найбільш ефективними непроникними кріопротекторами для кріоконсервування еритроцитів собак є поліетиленгліколь з м. м. 1500 (ПЕГ-1500) [1,2] та гідроксиетильований крохмаль (ГЕК) [15,21,28,31]. Ці речовини ефективні в низьких концентраціях і забезпечують захист клітин за допомогою часткової їх дегідратації перед заморожуванням.…”
Section: метод гіпотермічного зберігання дозволяє використовувати ком...unclassified